A practical framework for ranking universities by their competitive advantages: a mixed methods study on foundation universities in Turkey - ÖZDEMİR, ALİ (My University, 2022)
© 2022, Emerald Publishing Limited.Purpose: The purpose of this research is to determine the competitive advantages of higher education institutions (HEIs) and create a new methodology to rank universities according to the competitive advantages. Design/methodology/approach: The research determines the competitive advantages of HEIs by analysing expert opinions through a semi-structured interview form, matches codes and themes to performance indicators using Saldana\"s two-cycle coding methods, evaluates content validity through Lawshe and reveals the item weights of the ranking with analytical hierarchy process (AHP). Simple additive weighting (SAW) and Technique for Order of Preference by Similarity (TOPSIS) methods were used for ranking universities. Findings: Seven dimensions stand out in regard to what should be considered while ranking HEIs: research and publication, education, management, infrastructure, financial resources, human resources and social and economic contribution. Under the 7 dimensions, 69 indicators were determined. Practical implications: The research provides a scientific reference point where HEIs can compare themselves with other HEIs regarding where they are in the sector, especially in terms of competitive advantages. Originality/value: Although there are many different ranking methods that rank universities in the national and international literature, almost all these methods are largely based on the outputs of the university such as the number of publications, the number of patents, the number of projects, etc. A framework which ranks universities by considering different aspects of the institution, such as management, human resources and financial resources, has not been developed yet. In this respect, this research aims to fill this gap in the literature.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; İşletme; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; Management; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Genel Karar Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Strateji ve Yönetim; General Decision Sciences; Social Sciences & Humanities; Business and International Management; General Business, Management and Accounting; Strategy and Management; Competitive advantage; Higher education; Quality management; Strategic planning; University rankings